GEOLOGI KAMPUS TEMBALANG - Wahju Krisna H; Fahrudin Fahrudin (Diponegoro University, 2008)
Geological conditions at Tembalang areas and surround, Semarang, as a Undulating – Hillockymorphological. That’s can be representation lithological and structural conditions. This surveysused the Geoelectrical sounding and combined with geological surface mapping. There are 15points sounding of Geoelectrical, after interpreted with geological surface mapping, can beconclusion the Breccias lithologic overlay on the upper of Limestones lithologic and finding thereverse fault in the part north of areas survey.